Entrevista a la Dra. Carol Guarnizo-Herreño: Trayectoria Académica en Salud Pública y Recomendaciones para Investigadores Jóvenes de Latinoamérica - Ochoa-Escate, Dagny (2024)
Dr. Carol Guarnizo-Herreño, internationally recognized researcher in the area of public health, epidemiology and current co-coordinator of the Lancet Commission on Oral Health, shares her academic career, as well as reflections on the impact of political and commercial determinants on oral health inequities in Latin American countries. In this interview, organized by the Dental Public Health research group, Qhali Peru, Dr. Carol mentions her current project in the Lancet Commission; she also highlights the importance of working with the community in the search for solutions, strengthening collective action, better understanding the social determinants of health, and the responsibility and social commitment we all have.